Alternate approximate function for kernel function of oscillating lifting surfaces - Sulaeman, Erwin; Layeeq, Ahmed (2013)
Prediction of unsteady aerodynamic loads is still the most challenging task in flutter aeroelastic analysis. Generally the numerical estimation of steady and unsteady aerodynamic of thin lifting surface is conducted based on an integral equation relating aerodynamic pressure and normal wash velocity. The present work attempts to increase the accuracy of the prediction by using an approximate approach to evaluate kernel function occurring in the integral equation. Following previous approximation approach to solve the cylindrical function for planar lifting surface, in the present work such approach is extended to non planar lifting surfaces. To increase the accuracy of the method, the integration region of the kernel function is divided into two parts namely near and far regions, where a nonlinear regression curve fitting technique is adapted to approximate the denominator part of the cylindrical function of each region.